Attribution of the record breaking 2025 European fire season to climate change - Keeping,TR; Zachariah,M; Haas,O; Grillakis,M; Barnes,C; Clay,GD; Ekberzade,B; Jaupaj,O; Ribeiro,A; Trigo,R; Voulgarakis,A; Otto,FEL (Natural Hazards and Earth System Sciences, 2026)
Abstract. The 2025 European fire season was historically extreme, with record-breaking burned area exceeding 1 400 000 ha, and multiple regionally unprecedented wildfires. Emerging fire regimes and extreme wildfire behaviour in Europe pose increasing adaptation challenges. Extreme event attribution of a recent fire season, combined with analysis of changes in vegetation and land use, provides insight into the effect of climate and environmental change on high impact events. We analyse five regions that experienced particularly extreme wildfire activity in 2025 (northwestern Iberia, western and northern Britain, Occitania, the eastern Adriatic/Ionian, and northern and western Türkiye) capturing a diverse range of driving weather conditions and fire regimes. Strong trends towards drier summers and extreme weekly vapour pressure deficit (VPD) were found, with summer drought emergent from natural variability in most southern European regions, and VPD extreme emergent in reanalysis data for all regions. Changes in VPD are the main reason why combined hot, dry, and windy conditions have become more frequent than expected from natural variability. This emergence is seen in both reanalysis data and climate models for the Iberian, Adriatic/Ionian and Turkish regions. In contrast, in the British and Occitanian regions, models do not show observed trends.